Preparation method of tellurium-doped metal-nitrogen carbon catalyst and application of tellurium-doped metal-nitrogen carbon catalyst in zinc-air battery
By using tellurium-doped metal-nitrogen carbon catalyst on the cathode of the zinc-air battery, the problem of slow kinetics of the cathode oxygen reduction reaction of the zinc-air battery is solved, which significantly improves the catalytic activity and stability and improves the performance of the battery.
Patent Information
- Application Number
- CN202411869208.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The cathode oxygen reduction reaction (ORR) of zinc-air batteries has slow reaction kinetics, limiting its breadth and effectiveness in practical applications.
Tellurium-doped metal-nitrogen carbon (M-NC) catalyst is used as the cathode catalyst. This catalyst forms a transparent solution by dissolving the ligand in a mixed solvent and reacting with transition metal salts and zinc salts to form a MOF precursor, then mixing with tellurium dioxide and calcining at high temperature to obtain a tellurium-unitrogen carbon electrocatalytic material.
The catalytic activity and stability of the catalyst are improved, the power density and specific capacity of the zinc-air battery are enhanced, and the cathode catalytic performance is achieved.
Smart Images

Figure CN119725566A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of zinc-air battery cathode catalysts, and specifically relates to a method for preparing a tellurium-doped metal-nitrogen-carbon (M-NC) catalyst and an application thereof in zinc-air batteries. Background Art
[0002] The shortage of petroleum energy has made the development of new energy an urgent need for people, and the research, development and application of various new batteries are important contents. Zinc-air batteries have played an important role in the research of new batteries and their applications in electric vehicles, energy storage systems, etc. due to their advantages such as high energy density, low production cost and environmental friendliness. However, the slow reaction kinetics of the oxygen reduction reaction (ORR) on the cathode of zinc-air batteries seriously limits their extensive application and effectiveness in actual production and life, and the research and development of cathode catalysts with fast kinetics has become a key issue in improving their catalytic performance and stability.
[0003] Typical ORR catalysts are precious metal Pt-based catalysts and non-precious metal single-atom catalysts that have been studied in depth in recent years. Among them, metal-nitrogen-doped carbon (M-NC) catalysts are an important candidate material that can replace Pt-based precious metal catalysts. In recent years, in order to further improve the catalytic performance of metal-nitrogen-carbon materials, people have carried out structural regulation such as heteroatom doping, among which d-block transition metal doping has been studied more. However, due to its strong coordination ability, the doping of d-block elements often causes the reaction intermediates to be tightly bound, which affects the release and limits its reaction rate. Therefore, p-block metals with more p electrons and moderate coordination ability have attracted people's attention. The present invention provides a preparation of a p-block metal tellurium-doped metal-nitrogen-carbon catalyst and applies it to zinc-air batteries, showing good catalytic activity and stability, and provides a direction for the application of new ORR catalysts in zinc-air batteries. There is currently no relevant report in this regard. Summary of the invention
[0004] The technical problem solved by the present invention is to provide a novel method for preparing a p-zone metal tellurium-doped metal-nitrogen-carbon catalyst. The method successfully obtains a tellurium-doped M-NC single-atom catalyst and can be used as a cathode catalyst in zinc-air batteries. The doping of Te effectively regulates the electronic structure of the metal active site, improves the catalytic activity and stability of the catalyst, and broadens the material range of non-precious metal ORR catalysts.
[0005] The present invention adopts the following technical solution to solve the above technical problems, a method for preparing a tellurium-doped metal-nitrogen-carbon catalyst, characterized in that the specific steps are: Step S1: dissolving the ligand L in a mixed solvent I to form a transparent solution I, then dissolving the transition metal salt TM1 and the zinc salt in a mixed solvent II to form a transparent solution II, and then adding the mixed solution I to the mixed solution II to react to obtain a ZnTM1MOF precursor, wherein the ligand L is 2-methylimidazole or 1H-1,2,3-triazole, the transition metal salt TM1 is a nitrate or acetylacetone complex of Fe or Cu, the zinc salt is zinc nitrate or zinc chloride, the mixed solvent I is composed of methanol and N,N-dimethylformamide, and the mixed solvent II is composed of methanol, N,N-dimethylformamide and ethylene glycol; Step S2: After mixing and grinding tellurium dioxide and the ZnTM1MOF precursor obtained in step S1, the mixture is heated to 900-1000°C in an inert atmosphere and calcined for 2-3 hours to obtain a tellurium-uniformly doped metal-nitrogen-carbon electrocatalytic material, which is used as a cathode catalyst in a zinc-air battery.
[0006] It is further defined that the molar ratio of the transition metal salt TM1 to the ligand L in step S1 is 1:1-4.
[0007] It is further defined that the volume ratio of methanol to N,N-dimethylformamide in the mixed solvent I of step S1 is 1:1-2, and the volume ratio of methanol, N,N-dimethylformamide and ethylene glycol in the mixed solvent II is 1:1-3:1-2.
[0008] It is further defined that the turbid solution obtained after reacting for 24 hours in step S1 is centrifuged, washed with methanol for 3-5 times, and then placed in a vacuum drying oven to obtain a ZnTM1MOF precursor.
[0009] It is further defined that in step S1, the centrifugal speed is set to 8000 rpm / min, the centrifugal time is set to 5 min, and the temperature of the vacuum drying oven is set to 45-70°C.
[0010] It is further defined that the feed mass ratio of the ZnTM1MOF precursor to tellurium dioxide in step S2 is 1:1-4.
[0011] It is further defined that in step S2, the mixture of the ZnTM1MOF precursor and tellurium dioxide is placed in a tube furnace for high-temperature calcination, the heating rate is set to 1-5°C / min, and the inert gas is N2 or Ar.
[0012] The tellurium-doped metal-nitrogen-carbon catalyst of the present invention is used as a cathode catalyst in a zinc-air battery, and the power density of the assembled zinc-air battery reaches 141 mW cm -2 , and the specific capacity reaches 789mA hg -1 .
[0013] Compared with the prior art, the present invention has the following advantages and beneficial effects: The tellurium-doped metal-nitrogen-carbon catalytic material designed and synthesized by the present invention reduces the synthesis cost, and the synthesis method is simple and convenient. The tellurium-doped metal-nitrogen-carbon catalyst prepared by the present invention uses a metal organic framework as a substrate, has a high specific surface area and a rich pore structure, and significantly enhances the catalytic activity, mass transfer rate and durability of the catalyst. The tellurium-doped metal-nitrogen-carbon catalyst prepared by the present invention realizes the uniform distribution of p-region metal tellurium in the metal-nitrogen-carbon material, fully utilizes the moderate binding energy of the p-region metal, regulates the electronic structure of the metal site, and improves the catalytic performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 This is a scanning electron microscope image of the Fe / Te@NC material obtained in Example 1.
[0015] Figure 2 This is the transmission electron microscope image of the Fe / Te@NC material obtained in Example 1.
[0016] Figure 3 This is the open circuit voltage image of a zinc-air battery assembled with the Fe / Te@NC material obtained in Example 1 as a cathode catalyst.
[0017] Figure 4 This is the power density image of the zinc-air battery assembled with the Fe / Te@NC material obtained in Example 1 as the cathode catalyst.
[0018] Figure 5 This is the specific capacity image of the zinc-air battery assembled with the Fe / Te@NC material obtained in Example 1 as the cathode catalyst.
[0019] Figure 6 Linear voltammetric scanning curves of the Fe / Te@NC material obtained in Example 1 and the catalyst obtained in the comparative example at 1600 rpm in a 0.1 M KOH solution. DETAILED DESCRIPTION
[0020] The above contents of the present invention are further described in detail below through examples, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following examples. All technologies implemented based on the above contents of the present invention belong to the scope of the present invention. Example
[0021] 1.30 g of 2-methylimidazole was dissolved in a mixed solvent I (8.0 mL of methanol and 12.0 mL of N, N-dimethylformamide) to obtain a transparent solution I. 70.60 mg of ferric acetylacetonate and 1.20 g of Zn(NO3)2·6H2O were dissolved in a mixed solvent II (containing 12.0 mL of methanol, 36.0 mL of N, N-dimethylformamide and 12.0 mL of ethylene glycol) to obtain a transparent solution II. After ultrasonic treatment for 15 min, solution I was injected into solution II and the reaction was continued with stirring for 24 h. The resulting turbid solution was centrifuged and treated with methanol for 3-5 times until the upper solution was clear to obtain a white precipitate, which was dried in a vacuum oven at 70 °C to obtain a Fe-ZIF-8 precursor.
[0022] Tellurium dioxide and the obtained Fe-ZIF-8 precursor were mixed and ground in a mass ratio of 4:1 for 1 hour, then placed in a tubular furnace and heated to 950°C at a heating rate of 5°C / min under an Ar atmosphere and maintained for 3 hours, finally obtaining a Fe-NC single-atom catalytic material with tellurium uniformly dispersed and doped, marked as Fe / Te@NC. Example
[0023] The difference from Example 1 is that tellurium dioxide and Fe-ZIF-8 precursor are mixed in a mass ratio of 1:1 and ground for 1 hour to allow them to be fully in contact. Example
[0024] The difference from Example 1 is that tellurium dioxide and Fe-ZIF-8 precursor are mixed in a mass ratio of 2:1 and ground for 1 hour to allow them to be fully in contact. Example
[0025] The difference from Example 1 is that tellurium dioxide and Fe-ZIF-8 precursor are mixed in a mass ratio of 3:1 and ground for 1 hour to allow them to be fully in contact. Example
[0026] 1.00 g zinc chloride was dissolved in 10.0 mL N, N-dimethylformamide, 10.0 mL ethanol, 15.0 mL high-purity water and 5.0 mL ammonia water to mix them evenly, and then 1.3 mL 1H-1,2,3-triazole was added dropwise to the mixed solution. The mixture was stirred at room temperature for 24 h. The obtained product was washed with ethanol several times to obtain a white product, and vacuum dried to obtain a MET-6 precursor; 200.00 mg The MET-6 precursor was dissolved in 30.0 mL of methanol and continuously ultrasonicated to form a uniform mixed liquid. Then, 2.0 mL of a 20 mg / mL FeCl3·6H2O methanol solution was added. The obtained mixed solution was continuously stirred at room temperature for 12 h to obtain a Fe-MET-6 precursor, and then vacuum dried at 45 °C to obtain a Fe-MET-6 powder. The obtained Fe-MET-6 precursor was calcined at 900 °C for 3 h under nitrogen protection to form a Fe-NC catalyst. Tellurium dioxide and the obtained Fe-NC catalyst were mixed and ground at a mass ratio of 1:1 for 1 h to make them fully contact, and then pyrolyzed in a tubular furnace. Under nitrogen protection, the temperature was first raised to 300 °C and maintained for 30 min and then raised to 900 °C and maintained for 1 h to obtain tellurium-uniformly doped Fe-NC, which was recorded as Fe / Te@NC-2. Example
[0027] Weigh 6.5 g of 2-methylimidazole and dissolve it in 80.0 mL of methanol to obtain solution I. Dissolve 3 g of Zn(NO3)2·6H2O in 40.0 mL of methanol to obtain solution II. Inject solution I into solution II and continue to stir and react for 24 h. Centrifuge the resulting turbid solution and treat it with methanol 3-5 times until the upper solution is clear to obtain a white precipitate, which is vacuum dried at 50 °C to obtain a ZIF-8 precursor. Dissolve 300 mg of ZIF-8 precursor in 50.00 mL of ethanol, add 20 mg of Cu(NO3)2·3H2O, and stir and react for 24 h. h, washed three times with ethanol after centrifugation and dried to obtain a Cu-ZIF-8 precursor; tellurium dioxide and Cu-ZIF-8 precursor were mixed and ground at a mass ratio of 2:1 for 1 h, and then placed in a tubular furnace and heated to 950 °C at a heating rate of 5 °C / min under a N2 atmosphere and maintained for 2 h, finally obtaining a Cu-NC single-atom catalytic material uniformly doped with tellurium, which was marked as Cu / Te@NC.
[0028] Comparative Example 1 This comparative example uses 20 wt % commercial Pt / C as a control.
[0029] Comparative Example 2 1.30 g of 2-methylimidazole was dissolved in a mixed solvent I (containing 8.0 mL of methanol and 12.0 mL of N, N-dimethylformamide) to obtain a clear solution I. 1.20 g of Zn(NO3)2·6H2O was dissolved in a mixed solvent II (containing 12.0 mL of methanol, 36.0 mL of N, N-dimethylformamide and 12.0 mL of ethylene glycol) to obtain a transparent solution II. After ultrasonic treatment for 15 min, solution I was injected into solution II and continued to stir and react for 24 h. The resulting turbid solution was centrifuged and treated with methanol 3-5 times until the upper solution was clear to obtain a white precipitate, which was dried in a vacuum oven at 70 °C to obtain a ZIF-8 precursor.
[0030] The obtained ZIF-8 precursor was pyrolyzed in an argon environment, heated to 950°C at a heating rate of 5°C / min and maintained for 3 hours. After cooling, the powder was collected to obtain the nitrogen-doped carbon catalyst NC.
[0031] Comparative Example 3 1.30g 2-methylimidazole was dissolved in mixed solvent I (containing 8.0mL methanol and 12.0mL N,N-dimethylformamide) to obtain a clear solution 1. 1.20g Zn(NO3)2·6H2O and 70.60mg ferric acetylacetonate were dissolved in mixed solvent II (containing 12.0mL methanol, 36.0mL N,N-dimethylformamide and 12.0mL ethylene glycol) to form a transparent solution II, which was ultrasonicated for 15min, and solution I was injected into solution II and continued to stir and react for 24h. The obtained turbid solution was centrifuged and treated with methanol 3-5 times until the upper solution was clear to obtain a white precipitate, which was placed in a vacuum oven at 70℃ and dried to obtain the Fe-ZIF-8 precursor.
[0032] The obtained Fe-ZIF-8 precursor was pyrolyzed in an argon environment, heated to 950°C at a heating rate of 5°C / min and maintained for 3 hours. After cooling, the powder was collected to obtain the Fe-NC single atom catalyst.
[0033] Comparative Example 4 1.30 g of 2-methylimidazole was dissolved in a mixed solvent I (containing 8.0 mL of methanol and 12.0 mL of N, N-dimethylformamide) to obtain a clear solution I. 1.20 g of Zn(NO3)2·6H2O was dissolved in a mixed solvent II (containing 12.0 mL of methanol, 36.0 mL of N, N-dimethylformamide and 12.0 mL of ethylene glycol) to obtain a transparent solution II. After ultrasonic treatment for 15 min, solution I was injected into solution II and continued to stir and react for 24 h. The resulting turbid solution was centrifuged and treated with methanol 3-5 times until the upper solution was clear to obtain a white precipitate, which was dried in a vacuum oven at 70 °C to obtain a ZIF-8 precursor.
[0034] Tellurium dioxide and the obtained ZIF-8 precursor were mixed and ground at a mass ratio of 4:1 for 1 hour, then placed in a tubular furnace and heated to 950°C at a heating rate of 5°C / min under an Ar atmosphere and maintained for 3 hours, finally obtaining a nitrogen-carbon catalyst with uniformly dispersed tellurium, marked as Te@NC.
[0035] The catalyst prepared above is used as cathode catalyst in zinc-air battery, and the test contents of zinc-air battery include open circuit voltage, power density and specific capacity. The electrolyte required for the test is freshly prepared 6M KOH solution.
[0036] The catalyst was used as the cathode material of the zinc-air battery, and the loading amount of the cathode material was 1.1 mg cm -2 , a 10mm×10mm×0.1mm zinc sheet after polishing was used as the anode material, and a zinc-air battery was assembled for testing. The catalyst was applied to the zinc-air battery, and the method of assembling the zinc-air battery was as follows: the catalyst was added to the bottle, isopropanol was added thereto, and then Nafion was added thereto, and ultrasonicated for more than half an hour to fully mix it. The prepared slurry was coated on carbon fiber paper with good diffusion effect as the cathode of the zinc-air battery.
[0037] The tellurium-doped metal-nitrogen-carbon catalyst prepared in Example 1 of the present invention was applied to a zinc-air battery and exhibited a high power density (141 mW cm -2 ) and larger specific capacity (789mA hg -1 ).
[0038] The above embodiments describe the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for illustrating the principles of the present invention. Without departing from the scope of the principles of the present invention, the present invention may have various changes and improvements, and these changes and improvements all fall within the scope of protection of the present invention.
Claims
1. A method for preparing a tellurium-doped metal-nitrogen-carbon catalyst, characterized in that The specific steps are: Step S1: dissolving the ligand L in a mixed solvent I to form a transparent solution I, then dissolving the transition metal salt TM1 and the zinc salt in a mixed solvent II to form a transparent solution II, and then adding the mixed solution I to the mixed solution II to react to obtain a ZnTM1MOF precursor, wherein the ligand L is 2-methylimidazole or 1H-1,2,3-triazole, the transition metal salt TM1 is a nitrate or acetylacetone complex of Fe or Cu, the zinc salt is zinc nitrate or zinc chloride, the mixed solvent I is composed of methanol and N,N-dimethylformamide, and the mixed solvent II is composed of methanol, N,N-dimethylformamide and ethylene glycol; Step S2: After mixing and grinding tellurium dioxide and the ZnTM1MOF precursor obtained in step S1, the mixture is heated to 900-1000°C in an inert atmosphere and calcined for 2-3 hours to obtain a tellurium-uniformly doped metal-nitrogen-carbon electrocatalytic material, which is used as a cathode catalyst in a zinc-air battery.
2. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: In step S1, the molar ratio of the transition metal salt TM1 to the ligand L is 1:1-4.
3. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: In step S1, the volume ratio of methanol to N,N-dimethylformamide in the mixed solvent I is 1:1-2, and the volume ratio of methanol, N,N-dimethylformamide and ethylene glycol in the mixed solvent II is 1:1-3:1-2.
4. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: After reacting for 24 hours in step S1, the turbid solution obtained is centrifuged, washed with methanol 3-5 times, and then placed in a vacuum drying oven to obtain a ZnTM1MOF precursor.
5. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: In step S1, the centrifugal speed is set to 8000 rpm / min, the centrifugal time is set to 5 min, and the temperature of the vacuum drying oven is set to 45-70°C.
6. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: In step S2, the mass ratio of the ZnTM1MOF precursor to tellurium dioxide is 1:1-4.
7. The method for preparing the tellurium-doped metal-nitrogen-carbon catalyst according to claim 1, characterized in that: In step S2, the mixture of the ZnTM1MOF precursor and tellurium dioxide is placed in a tube furnace for high-temperature calcination, the heating rate is set to 1-5°C / min, and the inert gas is N2 or Ar.
8. A method for preparing a tellurium-doped metal-nitrogen-carbon catalyst, characterized in that The specific steps are as follows: 1.00 g zinc chloride is dissolved in 10.0 mL N, N-dimethylformamide, 10.0 mL ethanol, 15.0 mL high-purity water and 5.0 mL ammonia water to mix them evenly, then 1.3 mL 1H-1,2,3-triazole is added dropwise to the mixed solution, and the mixture is stirred at room temperature for 24 h. The obtained product is washed with ethanol several times to obtain a white product, and vacuum dried to obtain a MET-6 precursor; 200.00 mg The MET-6 precursor was dissolved in 30.0 mL of methanol and continuously ultrasonicated to form a uniform mixed liquid. Then, 2.0 mL of a 20 mg / mL FeCl3·6H2O methanol solution was added. The obtained mixed solution was continuously stirred at room temperature for 12 h to obtain a Fe-MET-6 precursor, and then vacuum dried at 45 °C to obtain a Fe-MET-6 powder. The obtained Fe-MET-6 precursor was calcined at 900 °C for 3 h under nitrogen protection to form a Fe-NC catalyst. Tellurium dioxide and the obtained Fe-NC catalyst were mixed and ground at a mass ratio of 1:1 for 1 h to make them fully contact, and pyrolyzed in a tubular furnace. Under nitrogen protection, the temperature was first raised to 300 °C and maintained for 30 min and then raised to 900 °C and maintained for 1 h to finally obtain a tellurium-doped metal-nitrogen-carbon catalyst.
9. A method for preparing a tellurium-doped metal-nitrogen-carbon catalyst, characterized in that The specific steps are as follows: 6.5 g of 2-methylimidazole was weighed and dissolved in 80.0 mL of methanol to obtain solution I, 3 g of Zn(NO3)2·6H2O was dissolved in 40.0 mL of methanol to obtain solution II, solution I was injected into solution II and the reaction was continued with stirring for 24 h, the resulting turbid solution was centrifuged and treated with methanol for 3-5 times until the upper solution was clarified to obtain a white precipitate, which was vacuum dried at 50°C to obtain a ZIF-8 precursor; 300 mg of the ZIF-8 precursor was dissolved in 50.00 mL of ethanol, 20 mg of Cu(NO3)2·3H2O was added, the reaction was stirred for 24 h, the mixture was washed with ethanol three times after centrifugation, and the Cu-ZIF-8 precursor was dried; tellurium dioxide and the Cu-ZIF-8 precursor were mixed and ground at a mass ratio of 2:1 for 1 h, and then placed in a tubular furnace and heated to 950°C at a heating rate of 5°C / min under a N2 atmosphere and maintained for 2 h, finally obtaining a tellurium-doped metal-nitrogen-carbon catalyst.
10. The tellurium-doped metal-nitrogen-carbon catalyst prepared by the method according to any one of claims 1 to 9 is used as a cathode catalyst in a zinc-air battery, and the power density of the assembled zinc-air battery reaches 141 mW cm -2 , and the specific capacity reaches 789mA hg -1 .
Citation Information
Patent Citations
Tellurium-doped oxygen reduction catalyst and preparation method thereof
CN113437316A
FeTe diatomic catalyst and preparation method thereof
CN116344845A
Preparation method of double-monatomic electro-catalysis material and application of double-monatomic electro-catalysis material in zinc-air battery
CN118231691A
Method for collecting platinum group metal by smelting tellurium-doped bismuth at low temperature
CN118563118A
Cathode Catalysts for Fuel Cells
US20140371057A1
Cited By
Preparation method and application of topological insulator composite catalytic material
CN120878860A
Preparation method and application of platinum / iron alloy coupled monatomic catalyst
CN121653742A